Third target - Rosenberg, Joel C. 1967- (Thorndike, Maine Center Point Large Prin, 2015)
"Risking his career and his life, a New York Times foreign correspondent investigates rumors that ISIS has acquired chemical weapons and tries to discover the intended target while under intense pressure from multiple governments not to publish his findings"--
"A novel."
104916
Keywords: Terrorism -- .; Journalists; Large type books; Christian fiction; Suspense fiction; Middle East; Large type books; Christian fiction; Suspense fiction; Thrillers (Fiction); Fiction